Reversible switching between pressure-induced amorphization and thermal-driven recrystallization in VO2(B) nanosheets - Yonggang Wang (Nature Portfolio, 2016)
Pressure can either make materials more disordered, like amorphization, or more thermodynamic stable, yet the switching between the two metastable phases has not been described. Wang et al. study it in vanadium oxide nanosheets and highlight the role played by spin and charge during the transition.